The Alliance supported a regional government in Peru to develop a bio trade strategy and 2028 action plan with regional partner - Wiederkehr Guerra, Gabriela Patricia; Ivanova, Yovita (2023)
To promote the sustainable use of native biodiversity, the Regional Government of Ucayali in Peru formed a Regional Technical Commission on BioTrade to develop a Regional Strategic Plan following an agroecological approach. The Alliance, together with the NGO Terra Nuova, supported the development of the strategy and its action plan. The plan aims to raise awareness on Amazonian native products, strengthen farmer organizations and institutions, and support local businesses.